Acute appendicitis in acute leukemia and the potential role of decitabine in the critically ill patient - Deepti Warad (Leukemia Research Reports, 2015)
Acute appendicitis in children with acute leukemia is uncommon and often recognized late. Immunocompromised host state coupled with the importance of avoiding treatment delays makes management additionally challenging. Leukemic infiltration of the appendix though rare must also be considered. Although successful conservative management has been reported, surgical intervention is required in most cases. We present our experience with acute appendicitis in children with acute leukemia and a case of complete remission of acute myeloid leukemia with a short course of decitabine. Decitabine may serve as bridging therapy in critically ill patients who are unable to undergo intensive chemotherapy.